Optimasi Pembelajaran IPS dengan Media Belajar Berbasis Teknologi Pertanian Hidroponik untuk Membentuk Generasi Tangguh Bencana - Sari Ratnawati; Suwarno Suwarno (UM Purwokerto Press, 2022)
SMP Negeri 4 Cilacap is located in a coastal area, with most of the population living as fishermen. The majority of students at SMP Negeri 4 Cilacap live in Rusunnawa and also in residential areas. The limited land they have makes them vulnerable to the basic food needs of students' families. This food scarcity can lead to serious problems that have an impact on food disasters. For this reason, in social studies subjects, teachers can raise the issue of this food disaster in classroom learning. The research objective of optimizing social studies learning with learning media based on hydroponic agricultural technology to form a disaster-resilient generation is to foster a disaster-resilient attitude towards food scarcity in the future and to create food security in students' families and society in general. This type of research is a qualitative descriptive research. Data obtained based on observations, interviews and literature review. The analysis technique used is not in the form of numbers and is subjective. The results of this study are expected to increase resilience towards food disasters in the future and can create food security for students' families and society in general.